2021
DOI: 10.4236/ajibm.2021.117051
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Export Diversification on Economic Growth: A Case of Southern African Development Community (SADC)

Abstract: The paper assessed "the influence of export diversification on economic growth in SADC". GMM approximation technique was adopted to obtain reliable approximations of the effect of export diversification on economic growth. Our study accounts for time-series variations in the data, captures country-specific time-invariant effects, and controls for endogeneity in the estimation model. The results show a significant effect of constructs of export diversification on economic growth. In addition, the study indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Most of the empirical inquiries (Arize, 1996) focused attention on industrial and advanced (particularly, European, Asian, American) economies. In addition, available extant studies based exclusively on African/Nigerian data (Abdullahi & Jibir, 2018;Doki & Tyokohol, 2019;Duru & Ehidiamhen, 2018;Hesse, 2008;Hodey et al, 2015;Huseyin & Shuaibu, 2020;Johnson, 2016;Lugeiyamu, 2016;Matezo et al, 2021;Nwosa et al, 2019;Odularu, 2009;Oyelami & Alege 2018;Owan et al, 2020;Vakataki'Ofa et al, 2016;Yuni et al, 2020) that have examined the nature of the relationship between export diversification and economic growth have focused mainly on investigating the growth impacts of overall export diversification which by its nature have been far from being definitive on comparative analysis of the effects of export diversification at intensive and extensive margins on growth. Specifically, no known study has been reported exclusively for Nigeria.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Most of the empirical inquiries (Arize, 1996) focused attention on industrial and advanced (particularly, European, Asian, American) economies. In addition, available extant studies based exclusively on African/Nigerian data (Abdullahi & Jibir, 2018;Doki & Tyokohol, 2019;Duru & Ehidiamhen, 2018;Hesse, 2008;Hodey et al, 2015;Huseyin & Shuaibu, 2020;Johnson, 2016;Lugeiyamu, 2016;Matezo et al, 2021;Nwosa et al, 2019;Odularu, 2009;Oyelami & Alege 2018;Owan et al, 2020;Vakataki'Ofa et al, 2016;Yuni et al, 2020) that have examined the nature of the relationship between export diversification and economic growth have focused mainly on investigating the growth impacts of overall export diversification which by its nature have been far from being definitive on comparative analysis of the effects of export diversification at intensive and extensive margins on growth. Specifically, no known study has been reported exclusively for Nigeria.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Espoir et al [8] examined "the impact of export diversification on economic growth in the Southern African Development Community (SADC) using the GMM approximation technique, while capturing time-series variations in the data, country-specific time-invariant effects, and controlling for endogeneity in the estimation model." The results showed that export diversification frameworks have a significant impact on economic growth.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Diversification of the economy means forming newly created added value (or GDP) in the country during the year, not in one or two areas but in a larger number of areas. Diversification of exports means the wide variety of products exported by the country to world markets, as well as the provision of the product (service), country, and regional diversity of export markets (Matezo et al, 2021;Makhlouf et al, 2015). Export diversification is a set of policies that involve changing the specific weight of individual goods in the existing export basket, offering new goods to the export basket, and gaining access to new geographic markets (Al-Marhubi, 2000; Bahar & Santos, 2017;Mau, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%